Reproductive Seasonality of Coral Assemblages in the Karimunjawa Archipelago, Indonesia - Wijayanti, Diah P.; Indrayanti, Elis; Wirasatriya, Anindya; Haryanto, Arfiyan; Haryanti, Dwi; Sembiring, Andrianus; Fajrianzah, Tyas A.; Bhagooli, Ranjeet (Frontiers in Marine Science, 2019)
Equatorial corals have been considered unlikely to spawn gametes synchronously at assemblage level. However, recent studies have reported multi-specific coral spawning events of corals in the tropics. Here, we document the reproductive activity of 25 Acropora species at Karimunjawa Archipelago over 4 consecutive years and the month of spawning for 3 Acropora species inferred from the presence of mature oocytes based on histological observation. Our study observed that Acropora assemblages demonstrated a high degree of inter-specific reproductive seasonality. The highest proportion of mature oocytes was observed in March 2011 (65%, n= 80). Oocytes were likely developed from May to March, 7-10 months prior the spermatogenesis. Spermatocytes were seen only from samples collected in March. Multispecific spawning events were observed during the first transition period (March – April) and the second transition period (September – October). Numbers of species contained mature oocytes was higher during March – April than September – October (16 species compared to 9 species respectively). Spawning rhythm was likely not followed the lunar cycle. Two distinct spawning events occurred when two periods of temperature rise was formed in March – April, and September – October. Daily temperature observation showed that spawning likely occurred on the day that experienced a temperature decrease prior the expected spawning time during temperature rise period. During temperature rise period, the wind speed was lower which may provide a signal for multi-specific spawning in the tropic at least at Karimunjawa Archipelago.